META-ANALYSIS OF 21ST CENTURY SKILLS IN YOUTH AND SPORTS - Bakar, Ryan Abu (ASEAN Journal of Sport for Development and Peace, 2023)
The purpose of this research is to find out the development of 21st century skills in the field of sports and youth. The researcher analyzed articles about 21st century skills related to sports and youth and how sports and youth activists are in the face of challenges and opportunities in today's modern digital era. The type of research used is meta-analysis based on literature review data. The researcher uses the Harzing Publish or Parist application where the researcher selects data sources from Google Schoolar, Science Direct, Scopus by entering the keywords 21st century skills, youth and sports with a time range from 2010 to 2023. From 100 existing articles the researcher selects again into 20 articles. the most supportive and related to 21st century skills in the field of youth and sports